If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4y = -2 Solving x + 4y = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. x + 4y + -4y = -2 + -4y Combine like terms: 4y + -4y = 0 x + 0 = -2 + -4y x = -2 + -4y Simplifying x = -2 + -4y
| 5x^2=16x+16 | | 98x^3+98x^2+20x=0 | | 98x^3+98x+20x=0 | | (x+2)(x)(3)=0 | | 4(x+21)=-3(x-21) | | 49x^2+49x+10=0 | | 128s^2+320s+200= | | 96r^2+336r+294= | | 3(6)-5y=15 | | 8(8x-3)=32x | | -7x-14=5x | | 2d^2+20d+50= | | 3s^2-8s=0 | | 4(x+1)+60=-4x | | 6+5y=9 | | w^2+14w+49= | | 3x-2=-13 | | 4r^2+23r+15= | | 21b^2-57b-18= | | 9b^2-15b-6= | | -4x^2-30x-14= | | 8(3x-4)=2(12x+3) | | 6a^2+79a+50= | | -26w=-7 | | 36v^2+84vt+49t^2=0 | | 6-19a+10a^2= | | 2(7+5x)=9x-4 | | 6+17n-1=9n+33-6n | | 0=-3x^2+8x-2 | | 0=-x^2-5x-2 | | 4w^3+9w^2+5w= | | x+3x=10-2 |